Development potential of wind energy in Turkey - İsmet Akova (EchoGéo)
Covering its energy requirement from fossil energy sources for the most part, Turkey relies on outside sources to procure energy required for its economy and different sectors. Similarly, Turkey had produced 83 pct of the overall electricity in 2008 out of fossil energy sources. Future projectors indicate that the energy requirement of our country would augment and foreign-dependency in energy would thus increase accordingly.  The on-going studies state that especially hydraulic power and wind energy potential, as part of the renewable energy sources of Turkey, are highly important and each of these two sources has the technical potential to cover the electric production in 2008. The recent increase in the number of wind energy power stations can be related to the preparation of Turkish Wind Atlas, the preparation of legal arrangements to support private sector entrepreneurs and the rise in oil prices. Wind energy power stations are active in Marmara, Aegean region and the Mediterreanean region witnessing more constant and strong winds and are anticipated to be founded in other geographical regions as well in the future.